Energy consumption levels and technical approaches for supporting development of alternative energy technologies for rural sectors of developing countries. (December 2018) - Muhumuza, Ronald; Zacharopoulos, Aggelos; Mondol, Jayanta Deb; Smyth, Mervyn; Pugsley, Adrian
Abstract: The delivery of modern energy services in developing countries (DCs) remains a pressing challenge. The traditional energy choices of 2.67 billion people most of whom living in rural areas of DCs have far-reaching implications to health, the environment and economies. Rural areas in DCs have renewable energy resources, which are largely untapped due to lack of energy demand information of requisite load centres. This article formulates indicative energy consumption data to support the design and development of novel alternative energy technologies for rural off-grid areas in DCs. The study examines energy demand/consumption through an extensive literature review of quantified energy needs in rural sectors of DCs including households, institutions, infrastructure and productive sectors. Various energy needs are identified and their typical consumption levels analysed. The study will stimulate further research and support the design and development of alternative energy supply technologies to mitigate energy poverty, trigger development and support sustainable energy for all (SE4All). Highlights: Energy consumption in rural sectors of developing countries (DCs) was examined. Typical energy demand in rural sectors of DCs is small for electrical applications but significant for solid fuels. Research activity about rural energy requirements for infrastructure and productive sectors is low. A matrix of typical energy demand was established for informing design questions. Technical opportunities are significant in renewable energy technologies and energy efficient appliances.